Multi-temporal urban growth analysis with expansion indicators in Lucknow constituency by open-source data, India - Ravi Verma; Pradeep Kumar Garg (Journal of Urban Management, 2022)
Urban sprawl in metropolitan cities of India is a distressing concern for planners. Not only, it is underachieved but it is neglected. This study attempts to help in understanding the gap by studying urban sprawl in 5 assembly constituencies (ACs) of Lucknow city of India, through urban growth indicators such as urban growth types (Infilling, Edge-expansion and outlying), Shannon's Entropy value and Landscape metrics (Complexity, Compactness, Centrality and Porosity). Results for these 5~​ACs namely Cantonment (Cantt.), Lucknow Central (LC), Lucknow East (LE), Lucknow North (LN) and Lucknow West (LW) show that constituency has gone under a large amount of urban growth since 1985 to 2015. Amount of edge expansion in 2005-2015 is decreasing from previous duration of changes in year 1985-1995 and 1995-2005. Outlying growth of built-up area shown by formation of new patches is resulting in increase of 122.69 km2 area in Built-up from 1985 to 2015, which was at first cycle (1985-1995) caused by decrease in Other and Vegetation Land Use (LU) class but after that in 1995-2005 and 2005-2015, it is mainly due to decrease in Agricultural land. Among Landscape metrics, NP (Number of Patches) and LSI (Landscape Shape Index) show upward trend from 1985 to 2015 indicating increase in compactness and complexity of patches of Built-up but ENN_MN (Mean Euclidean Nearest neighbor Distance) and AI (Aggregation Index) show either constant or negative trend. Shannon's entropy value Hn for every year is close to loge(n) and also in increasing manner, depicting increase in Built-up area dispersion.
Keywords: 710; Land use; Landscape metrics; Multi-temporal; Remote sensing; Urban sprawl